Intrinsically photosensitive retinal ganglion cells and visual processing: ipRGCs beyond non-image-forming functions - Lee, Hsing-Hao (Frontiers in Neuroscience, 2025)
Intrinsically photosensitive retinal ganglion cells (ipRGCs) are relatively newly discovered photoreceptors other than rods and cones. For the last decade, people have been considered ipRGCs to be primarily in charge of non-image-forming and cognitive functions. However, an increasing body of evidence has pointed out that ipRGCs also play a role in visual processing, such as contrast, brightness and color perception. In this mini-review, I listed what the caveats about those studies discussing how ipRGCs affect cognitive functions and how ipRGCs serve as image-forming functions under well-controlled condition.